1952
DOI: 10.1021/ie50515a056
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated and Outdoor Weathering of Colored Vinyl Films

Abstract: THEoutdoor uses of plasticized vinyl chloride polymers and copolymers have been increasing and the evaluation and prediction of outdoor weathering life, have, therefore, assumed greater importance. While many of the outdoor uses are for consumer INDUSTRIALAND ENGINEERING CHEMISTRY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1955
1955
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The absorption of dibasic lead phosphite takes a pronounced upward sweep in the ultraviolet region which undoubtedly has a bearing on the favorable results obtained with this substance. It would be interesting to carry these determinations to at least 290 µ, the lower limit of sunlight, to determine if the indicated trends are real since light below 350 mg is credited with being the most damaging to vinyl polymers (4)• Since the structure of dibasic lead phosphite indicates that it might function as an antioxidant or free radical trap, its activity in this direction also was investigated. The oxygen absorption method employed by Biggs and Hawkins (ß) in studying the oxidative aging of polyethylene was employed for evaluating antioxidant activity.…”
Section: Stabilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption of dibasic lead phosphite takes a pronounced upward sweep in the ultraviolet region which undoubtedly has a bearing on the favorable results obtained with this substance. It would be interesting to carry these determinations to at least 290 µ, the lower limit of sunlight, to determine if the indicated trends are real since light below 350 mg is credited with being the most damaging to vinyl polymers (4)• Since the structure of dibasic lead phosphite indicates that it might function as an antioxidant or free radical trap, its activity in this direction also was investigated. The oxygen absorption method employed by Biggs and Hawkins (ß) in studying the oxidative aging of polyethylene was employed for evaluating antioxidant activity.…”
Section: Stabilizersmentioning
confidence: 99%
“…Natural Weathering. The elongation-retention properties of the pigmentation series based on 3 years' (1961-53) exposure data from New Jersey, Florida, and Arizona are plotted in Figures 4 and 5. From these curves, obtained from averages of at least three specimens of each sample from each location, it is apparent that both the nature and concentration of the pigment has a major effect on weathering.…”
Section: Pigmentsmentioning
confidence: 99%
“…A wider discussion of acceptable limits of exposure is needed in the field.Years ago there was an idea put forth that very little fading of paints and textiles would occur upon outdoor exposure if the level of sunlight intensity fell below 0.823 gram calories/cm 2 /min. Although this suggestion has been associated withClark (1952), the idea apparently came from DeNoon of the South Florida Test Service. A possible reason why this specification may have proven to be reasonably correct is that, as the intensity of sunlight outdoors increases, the temperature of samples on exposure also increases.…”
mentioning
confidence: 99%
“…9] and the sample presentation to the sunlight is controlled with regard to azimuth and hearing. The use of total incident radiation as an exposure index has improved the reliability of outdoor exposure testing but investigators have reported that, even at a constant level of total incident radiation, degradation seems to proreed faster in summer than in winter [ 3 ] . In addition, large differences due to test location have been observed [ 3 ] .…”
mentioning
confidence: 99%
“…The use of total incident radiation as an exposure index has improved the reliability of outdoor exposure testing but investigators have reported that, even at a constant level of total incident radiation, degradation seems to proreed faster in summer than in winter [ 3 ] . In addition, large differences due to test location have been observed [ 3 ] . The authors have noted that the amount of degradation for a given level of total incident radiation is much higher in South Florida than in Arizona.…”
mentioning
confidence: 99%